Performance of radon monitors in a purpose-built radon chamber. (31st August 2018) - Fuente, Marta; Rabago, Daniel; Herrera, Sixto; Quindos, Luis; Fuente, Ismael; Foley, Mark; Sainz, Carlos
Abstract: The purpose of this paper is to benchmark several different radon monitors, by quantifying their accuracy and response time. Radon monitors with different characteristics were tested in a purpose-built radon chamber under reference conditions. The radon concentration in the chamber was controlled and maintained at a stable radon concentration of (2648 ± 85) Bq m −3 to evaluate the accuracy and precision of these monitors. The response time of the monitors was analysed for two time intervals. To assess the response time of the monitors, radon concentration was varied from a theoretical value of 0–6441 Bq m −3 and then from 6441 to 2648 Bq m −3 . The results from this study show that general purpose radon monitors are less accurate than those used by radon testing service providers and the research community. All monitors tested reported a mean radon concentration within the ±10% of the reference detector value at the radon equilibrium concentration. Different response time analysis methods were proposed and discussed, and for the particular time intervals analysed, response time was found to be slower for those radon monitors intended for general purpose applications.